(untitled) (Delito y Sociedad, 2022)
This paper focuses on the «prisoner-entrepreneur» as an agent in the governance relations in a men’s prison in Montevideo, Uruguay. This is Punta de Rieles, a non-traditional prison in which prisoners’ responsibilization plays a fundamental role as a strategy of governance deployed by state authorities and agents to make prisoners responsible for developing, with broad levels of autonomy, an open range of activities officially promoted. The production of goods and services stands out among them. Most are generated from prisoners’ initiatives. To obtain the prison authorities’ authorization and support to carry it out, prisoners are encouraged to design the productive activity project and draft a formal request. This «prisoner-entrepreneur» occupies a unique position in prison population. He is subject to responsibilization, requested to engage in a «positive use» of time and to develop forms of self-governance. However, simultaneously, as «employers» of other prisoners, they become and act as governance agents and they structure the field of action of the «prisoner-employee». In turn, this governmental role implies a whole series of collaborative but also conflictive relationships with state agents, especially with prison officers. This paper addresses the peculiar position of the «prisoner-entrepreneur» in terms of his governmental role and his links with state agents, as a unique form of governance in this non-traditional Latin American prison.